Aboriginal life pathways through multiple human service domains; administrative data linkage for policy - Mitrou, Francis; Zubrick, Stephen; Pearson, Glenn; Ferrante, Anna; O’Donnell, Melissa; Johnson, Sarah; Milroy, Helen; Brown, Ngiare; Carapetis, Jonathan (International Journal of Population Data Science, 2018)
Aboriginal children and families face the highest levels of disadvantage of any population group in Australia across health, education, child protection, justice and other human service domains, but longitudinal data to inform policy is scant. The Western Australian Aboriginal Child Health Survey (WAACHS) is a population representative cross-sectional child development study of over 5,000 randomly selected children aged 0-17 years, plus their families and schools, conducted between 2000 and 2002. This project seeks to leverage the WAACHS by linking the survey data for all participants with State administrative human services data registers from the previous 30+ years, to develop a major program of work in Aboriginal Human Development that would be unique in the world. This presentation describes the project history, novel survey linkage methodology, and project aims in the policy domain.